Understanding Learners’ Metacognition of Online Teacher Feedback Amid COVID-19: A Case Study in a University Livestream Instruction Context - Wang, Feng; Meng, Fanding; Liu, Shichuan; Wang, Shiqi; Pan, Lihui; Lin, Zhong (Frontiers in Psychology, 2022)
While research on metacognition in second language (L2) learning has burgeoned in the past two decades, its relation to actual teaching behaviors, such as teacher feedback, remains to be fully described and explained in L2 classroom, especially in livestream English teaching settings. To fill this gap, this case study examined how learners utilize and regulate metacognition of online teacher feedback during COVID-19 in a Chinese inner land university. Data were gathered through semi-structured interviews. With qualitative and interpretive analysis, it is revealed that leaners positively receive online teacher feedback for its detrimentalness together with a growth mindset and high levels of resilience, but, on the whole, there is a metacognitive deficit: they misinterpret self-consciousness about online feedback which is underpinned by a conception of tasks that characterizes online L2 learning. This research expands our understanding of L2 learning processes pertaining to awareness and management of teacher feedback receiving and may also shed light on solutions to empower livestream teaching by building external scaffolding devices to compensate weaknesses of online L2 education during the pandemic and beyond.